MODERN SLAVERY AND AUSTRALIA’S STRATEGIC RESPONSE DURING COVID-19 PANDEMIC 2020-2023 - Emanuella Amanda Saraswati; Reza Triarda (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2026)
This article examines Australia’s strategic response to modern slavery during the Covid-19 pandemic from 2020 to 2023 through the Theory of Change framework. The study identifies a central Pandemic Paradox where enhanced institutional detection and reporting capacity coexisted with persistent structural vulnerabilities. Empirically, the research documents an underanalyzed crisis period, while theoretically, it extends the Theory of Change to conditions of global systemic disruption. Findings reveal that while deterrence and global regulatory strategies significantly improved case visibility, transparency-based approaches remained insufficient without binding due diligence to address the socio-economic drivers of exploitation. At the regional level, Australia’s leadership in the Bali Process with Indonesia strengthened intermestic governance, yet its efficacy remains contingent upon proactive protections for migrant workers. This study provides a strategic policy roadmap for middle powers to balance domestic enforcement with multilateral coordination. In conclusion, a transition toward rigorous legal accountability is essential to break the cycle of modern slavery paradoxes during global crises.